2020
DOI: 10.1111/chso.12408
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity among ‘boys’ in Papua New Guinea: Memories of sameness and difference in early childhood

Abstract: Childhood is a time when children begin to constitute themselves as gendered subjects largely according to social norms that are rigidly framed within dominant discourses of heteronormative binary gender. This paper is based on the life histories of 42 sexuality and gender diverse adult men and transgender women conducted in PNG. Findings offer insight into the ways in which boys transgressed gender norms through dress, play, work within the home and in dance. We argue that gender transgression in childhood is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Transgressions from cisgender and heteronormative behaviors expose children and adolescents to stigma and bullying, which may account for the previously identified associations between these items and poorer mental health. For 3 decades, qualitative studies in the social sciences have demonstrated the negative impact of homophobic and transphobic harassment and violence experienced by children who transgress gender norms, which affects their health and educational outcomes . To support the health and well-being of sexuality- and gender-diverse young people, further quantitative research is warranted to understand the mechanisms of this association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgressions from cisgender and heteronormative behaviors expose children and adolescents to stigma and bullying, which may account for the previously identified associations between these items and poorer mental health. For 3 decades, qualitative studies in the social sciences have demonstrated the negative impact of homophobic and transphobic harassment and violence experienced by children who transgress gender norms, which affects their health and educational outcomes . To support the health and well-being of sexuality- and gender-diverse young people, further quantitative research is warranted to understand the mechanisms of this association.…”
Section: Discussionmentioning
confidence: 99%
“…Children self-report on surveys from primary school age, and neurotypical children are aware of their gender by 3 years of age. [71][72][73] More accurate parent-report measures could also be developed, informed by recent work in Australia 27 and elsewhere, 74 to capture accurate gender identity (sex recorded at birth and current gender identity in a 2-step process). 10 However, it is clear that gender role nonconformity occurs from early childhood, regardless of whether it is linked to later sexuality or gender diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation